IMPLEMENTASI KEGIATAN PRABELAJAR SEBAGAI INOVASI BUDAYA SEKOLAH DALAM PENGUATAN KARAKTER MURID DI SD NEGERI 3 PANCOR - Etin Seftiani; Putri Niva Nurviani; Zuhdina Sulastini; Lalu Parhanuddin; Syamsul Hadi (Jurnal Manajemen Pendidikan, 2026)
Character education is one of the main priorities in the Indonesian education system. However, previous studies have generally focused on individual habituation activities rather than examining pre-learning activities as an integrated school culture system. This study aimed to analyze the implementation of pre-learning activities as a school culture innovation to strengthen students' character at SD Negeri 3 Pancor, East Lombok Regency. A descriptive qualitative approach was employed. Data were collected through observations, semi-structured interviews, and documentation involving the principal, teachers, and students selected through purposive sampling. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña. The findings indicate that integrated pre-learning activities strengthen students' religious values, nationalism, discipline, responsibility, health awareness, creativity, and self-confidence. The study concludes that integrating various pre-learning activities into the school culture is an effective strategy for strengthening students' character in a sustainable manner.